Cold-pressed rice bran oil-in-water emulsion delivery system with anti-inflammatory activity in THP-1 macrophages - Kaewsaen, Raweephorn; Klinkesorn, Utai; Chanput, Wasaporn Preteseille (Agriculture and Natural Resources, 2022)
Importance of the work: Cold-pressed rice bran oil has been widely consumed, however its pathway involving anti-inflammatory activity has not been elucidated. Objectives: To investigate the potential of CPRBO emulsion as a delivery system and its anti-inflammatory effects after in vitro digestion. Materials & Methods: Commercial CPRBO was purchased from a local supermarket in Thailand. The CPRBO emulsion was fabricated by homogenizing technique. The cytotoxicity was tested through the MTT assay. The anti-inflammatory activities of digested CPRBO emulsion were evaluated by quantitative real-time polymerase chain reaction and western blot analysis. Results: CPRBO from Khao Dawk Mali 105 rice variety contained phytochemicals (including gamma-oryzanol, phytosterols and alpha-tocopherol) and had a suitable fatty acid profile. The CPRBO emulsion had particle sizes of approximately 166 nm and remained stable for 4 wk at 4°C. The emulsification efficiency was higher than 99%. The emulsion withstood the gastric phase of digestion with no significant increase in particle size and polydispersity index. However, these parameters were significantly increased in the small intestinal phase due to the activity by lipid-digesting enzymes and bile extracts, suggesting that the CPRBO emulsion remained stable until reaching the small intestine. The digested CPRBO emulsion significantly suppressed pro-inflammatory cytokine gene expression via inhibition of NF-κB p65 expression and phosphorylation. Main finding: In addition to reviewing the pathway involving anti-inflammatory effects, this study demonstrated the potential applicability of CPRBO-in-water emulsion as a delivery system for lipophilic bioactive compounds.